Record of Late Pleistocene Ice Rafted Debris at IODP Site 1308 in the Central North Atlantic - Bechtel, Katherine (The Ohio State University, 2015)
Ice rafted debris (IRD) consists of rock grains of terrestrial origin that were transported by glacial icebergs. These grains may provide clues to past climate, ocean currents and other geologic conditions. Samples from the North Atlantic Integrated Ocean Drilling Program (IOPD) Site 1308 have been examined to collect information on IRD abundances downcore. In this study a total of 39 samples have been inspected and range in age from 851.5 to 969.625 kya. These data were compared to known glacial stage data in order to see if the abundance of ice rafted debris corresponds to global climate state through time. The abundances of specific grain types were acquired through a census of 100 grains from each sample, which were taken at a spacing of10 to 30 cm in the core. The terrestrial grains showed fluctuations in abundances within the core. Terrestrial abundances increased near the boundaries of the glacial/interglacial stages for both the individual grain categories and the terrestrial group as a whole. Some IRD grain types are site-specific, allowing the determination of iceberg provenance. The grains were found to originate from Canada, Iceland/central East Greenland, and southern Greenland. Integrated Ocean Drilling Program No embargo